PENINGKATAN HASIL BELAJAR TEMATIK TERPADU SISWA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE MAKE A MATCH - Shandy, Imam Kurnia; Zuardi, Zuardi (Universitas Negeri Padang, 2021)
The purpose of this study is to describe the increase in student learning outcomes using the Cooperative Learning model Make A Match type in integrated thematic learning in class IV SDN 16 Koto Langang, Pesisir Selatan Regency. This type of research is classroom action research (CAR) using qualitative and quantitative approaches. The subjects of this study were teachers as observers, researchers as practitioners, and 21 grade IV students. The study was conducted in two cycles. The results of this study are: (1) Percentage of RPP assessment in the first cycle 81.25% (B) Increased in the second cycle 92.5 (SB). (2) The aspect of teachers in the first cycle 82.5% (B) increased in the second cycle 95% (SB). (3) Aspects of students in the first cycle 82.5% (B) increased in the second cycle 92.5% (SB). (4) Student learning outcomes in the first cycle with an average of 74 increased in the second cycle 81.93.